Thermal, mechanical, and morphological properties of aerospace clip panels using woven carbon fibre reinforced PPS - Hamdan, Hasanudin; Razali, Nadlene; S, M. Sapuan; Arith, Faiz; Kamarolzaman, Anita Akmar; Sharif, Emy Aqillah; Ahmad Rashidi, Syazwan; Othman, Sarah; Muhammad, Noryani; Abdul Aziz, Noor Zuhaira; Mezeix, Laurent (SAGE Publications Ltd, 2026)
The use of advanced thermoplastics in aircraft applications is steadily increasing due to their excellent mechanical strength and thermal stability. This study investigates Carbon Fibre Reinforced Polyphenylene Sulfide (CF/PPS) composites utilising a 5-Harness Satin (HS) fabric. Quasi-isotropic laminates with two different thicknesses underwent a thermoforming process at varying tool temperatures. The objective is to evaluate the effect of the degree of crystallinity (DOC) on the mechanical properties, specifically Impact Strength and Interlaminar Shear Strength (ILSS), as well as on thermal properties through Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC) analysis. The results show that the DOC of CF/PPS in both 6- and 8-ply samples led to an improvement of over 50% in impact strength. Furthermore, ILSS increased by 15.3% and 10.38% at tool temperatures of 170°C and 160°C for the 6 plies and 8 plies laminates, respectively. TGA analysis after stamping indicated improved thermal stability with higher residual content, suggesting enhanced char formation. Lastly, for DSC results, DOC demonstrated 22.8% crystallinity after the thermoforming process, further supporting the correlation between DOC and mechanical performance.